Comparison between Concept of Evaluation on KTSP Curriculum and 2013 Curriculum - Linda Aprillianti (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
This study tries to explain in detail related to the differences between concept of evaluation on KTSP and 2013 Curriculum. the curriculum may is referred to as a set of plans and arrangements concerning the objectives, content, and lesson materials and methods used as guidelines for the implementation of learning activities to achieve specific educational objective. Evaluation Curriculum is a systematic study of the benefits, the suitability of effectiveness and efficiency of the curriculum applied. Focus of this study is describing the comparison of concept evaluation in KTSP and 2013 Curriculum and also describing the strength and weakness of both curriculums. The method used by the writer belongs to qualitative descriptive. The result of the study explains in short description and table comparison. Based on the e result of this study, it shows that between curriculum KTSP and 2013 both have their own goals. So that, between KTSP and 2013 Curriculum have different aspect to assess. So the evaluation between KTSP and 2013 Curriculum is relative different. As the conclusion, the curriculum can run well depend on the teachers themselves. Although we create an excellent curriculum, but if it handled by less qualified teacher, it will not produce adequate results. Conversely, in the hands of qualified teachers, the usual curriculum will produce good results. Thus, the existence of a new curriculum, as the Curriculum 2013 not necessary.